2017
DOI: 10.1002/jbm.a.36211
|View full text |Cite
|
Sign up to set email alerts
|

Design principles for lymphatic drainage of fluid and solutes from collagen scaffolds

Abstract: In vivo, tissues are drained of excess fluid and macromolecules by the lymphatic vascular system. How to engineer artificial lymphatics that can provide equivalent drainage in biomaterials remains an open question. This study elucidates design principles for engineered lymphatics, by comparing the rates of removal of fluid and solute through type I collagen gels that contain lymphatic vessels or unseeded channels, or through gels without channels. Surprisingly, no difference was found between the fluid drainag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…The attributes of microfluidic models make them readily capable for precise quantitative analysis of the mass transport properties of the interstitium . This principle was recently demonstrated by Thompson et al where the fluid drainage properties of microengineered blind‐ended lymphatic vessels embedded within collagen scaffolds were characterized. Interestingly and somewhat surprisingly, the solute drainage rates were greater in collagen gels that contained lymphatic vessels than in those that had bare channels by preventing solute transport back into the scaffold.…”
Section: Microfluidic Approaches For Studying Lymphatic Vasculaturementioning
confidence: 99%
“…The attributes of microfluidic models make them readily capable for precise quantitative analysis of the mass transport properties of the interstitium . This principle was recently demonstrated by Thompson et al where the fluid drainage properties of microengineered blind‐ended lymphatic vessels embedded within collagen scaffolds were characterized. Interestingly and somewhat surprisingly, the solute drainage rates were greater in collagen gels that contained lymphatic vessels than in those that had bare channels by preventing solute transport back into the scaffold.…”
Section: Microfluidic Approaches For Studying Lymphatic Vasculaturementioning
confidence: 99%
“…The amount of solute that remains typically decays exponentially with time, and the rate constant or half-life of this decay provides a measure of drainage (386). Measurement of drainage constants through individual lymphatics is possible (581). Individual collecting lymphatics can be cannulated for measurement of their contraction amplitudes and frequencies (161,667).…”
Section: Objectives Of Vascularizationmentioning
confidence: 99%
“…In narrower channels, ECs can form plugs, which require additional signals to promote cell migration along the channels (346). Seeding lymphatic ECs into blind-ended channels generated lymphatics (581). An alternate strategy used electrical desorption to transfer a monolayer of ECs from a thin metal rod onto a channel in collagen gel (502).…”
Section: Decellularization Of Organsmentioning
confidence: 99%
“…[108,109,184,197] Previous work has shown that collagen hydrogels can promote lymphatic vessels that can support drainage of fluid in vitro for potential regenerative tissue engineering applications. [184][185][186] Another study seeded LECs and dermal fibroblasts into collagen hydrogels where the cells were able to form lumen-forming lymphatic capillaries within the hydrogels. [190] Additionally, collagen hydrogels encapsulating a section of isolated mouse thoracic duct supported the formation of lumenized lymphatic capillaries in vitro and have applications for identifying new therapeutic and genetic lymphangiogenic regulators.…”
Section: Cell-based Therapiesmentioning
confidence: 99%